Study on formation of urban tissue in Bhaktapur in Kathmandu Valley, Nepal - Kido, Anri; Yamamoto, Naohiko; Masui, Masaya; Takeuchi, Yasushi Takeuchi (Journal of Science and Engineering, 2012)
This paper makes a study of street patterns and organization of dwelling units of the historic city of Bhaktapur, a World Heritage Site in Kathmandu Valley. Spatial syntax is used to analyze the street patterns, which shows the western part of the city as structured along its main street while the eastern part more nucleated with squares as centers of the settlement. With this clue that suggests the development phase of Bhaktapur city, the patterns of dwelling clusters of the eastern part are studied. The study taking into account of specific settlement culture of Newars, the traditional inhabitants of the Valley, then makes a typological differentiation of the dwelling clusters that are also related to development phase of the settlement. The paper then studies the location of the shrine of Ganesa—an essential religious feature of the neighborhood. Further, user households of other community facilities, such as pati—the resting place, and hiti—the water fountain, are identified and the respective user community compared with respect to the neighborhood boundaries.